Performa Ayam Broiler yang Diberi Metabolit Aceto-Sacch dalam Air Minum - N Ramli; A Sofyan; E Anggraini (Media Peternakan, 2007)
This research was conducted to study the effect of addition of Aceto-Sacch metabolite (m-AS) product into drinking water on performance, percentage of intestine and caeca of broilers. One hundred and fifty birds of day old chicks (DOC) of 'Hubbard' strain were divided into 5 groups of treatments. The treatments were R0 (control diet + drinking water without Aceto-Sacch metabolite / 0% m-AS), R1 (R0 + 12.5% m-AS), R2 (R0 + 25% m-AS), R3 (R0 + 50% m-AS), Rk (commercial diet + 0% m-AS). Chicken were given diet and drinking water ad libitum. Feed intake, body weight gain and feed conversion were measured weekly. Throughout four weeks feeding trial, two animals from each group were taken and decapitated for measuring percentage of intestine and caeca. Data from completely randomized design were analyzed statistically by analysis of variance (ANOVA) and contrast orthogonal. Results showed that drinking water containing more than 25% m-AS (R2 and R3) reduced body weight, feed intake and increased percentage of small intestine and caeca. However, m-AS addition at 12.5% improved feed conversion ratio and slightly increased body weight gain. Addition of 9.0 % m-AS in total drinking water was the optimum level increasing performance of broiler. It is concluded that addition of 12.5 % m-AS product into drinking water could slightly increased body weight gain and improve feed efficiency of broiler chicken.Key words: broiler performance, drinking water, aceto-sacch